Pengaruh Model Pembelajaran Sinektik Terhadap Kemampuan Menulis Puisi Peserta Didik Sekolah Dasar - Gea, Fortin Wan Boi; Zendrato, Jhoniel Samolala; Gulo, Kelvin; Waruwu, Vinsensius; Hulu, Enjel Desman Samkhalis; Mendrofa, Elfanus; Gea, Endang Purnawati; Zalukhu, Festi Hidayat; Harefa, Edward (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research is based on the influence of the synectic learning model on the ability to write poetry of grade V students of SD Sisobahili, Gunungsitoli City. With the number of samples at the school amounting to 58 respondents (students). The purpose of this study is to find the influence of the synectic learning model on the writing ability of elementary school students. The data collection technique used in this study is using a quantitative approach. In this study, the data collection method used is a questionnaire (questionnaire). Based on the results of the research conducted, it can be concluded that the influence of the synectic learning model on the poetry writing ability of elementary school students. In the ongoing learning process, of course, the synectic learning model is very suitable for use in teaching and learning activities. Because this learning model is an approach that prioritizes improving aspects of student creativity and self-development.